Analysis of objects food industry dangers and estimation of risks origin on them emergency situations - Volodchenkova, Natalia; Hivrich, Olexandr; Levchenko, Oleg (My University, 2013)
Аnalysis of the risk of accidents in the food industry, the development and implementation of measures to prevent them requires considerable effort and cost, which is the reason for the decline of profitability on a certain time, but early resolution of these issues can eliminate existing contradictions and ensure effective operation of the enterprise and its further development. Integrated application of risk assessment of emergency situations in the food industry can develop and justify effective measures to improve the safety of their operation.
Keywords: safety; безпека; безопасность; safe working environment; безпечні умови праці; working conditions; resource support; ресурсна підтимка; кафедра екології та екоменеджменту